Concept map: alternative assessment tool in laboratory learning of electrolysis - Ghani, I. B. A. (American Scientific Publishers, 2016)
In-depth understanding of concepts studied is the main goal of a learning process. One of the alternative assessment tools that could potentially increase students’ level of understanding is through the use of concept maps. Accordingly, the main objective of this research was to examine the effects of using concept maps in assessing the level of students’ understanding of electrolysis through laboratory learning activities. A total of thirty two Form 4 students were involved in the study. The pre and post concept map task that was evaluated using convergence scoring method was the instrument used in this study. The results of the study found that, the level of students’ understanding could significantly be increased due to the use of concept maps as an alternative assessment tool for laboratory learning activities. In-depth understanding bears close relationships with the ability of an individual to have higher-order thinking skills. In addition, the positive feedbacks provided by the students on their ability in using concept maps to assess their understanding in laboratory learning activities were also reported in this study.